Research on the Impact Mechanism of Integrative and Instrumental Motivation on the Persistence of Chinese Language Learning Among International Students in China - Hu, Xiaoli; Liu, Rui; Zhang, Yuanyuan (Journal of Educational Research and Policies, 2025)
From the perspective of motivation theory, this paper explores the influence of integrative and instrumental motivation on Chinese language learning. First, it elaborates on the connotations and characteristics of integrative and instrumental motivation. Second, it analyzes the manifestations of motivation’s impact on the persistence of Chinese language learning from both integrative and instrumental perspectives. Finally, the impact mechanism of motivation on Chinese language learning is examined in detail at psychological and behavioral levels, further revealing the critical role of motivation in Chinese language acquisition.